MUC1‐C is a target in lenalidomide resistant multiple myeloma. (23rd June 2017) - Yin, Li; Tagde, Ashujit; Gali, Reddy; Tai, Yu‐Tzu; Hideshima, Teru; Anderson, Kenneth; Avigan, David; Kufe, Donald
Summary: Lenalidomide (LEN) acts directly on multiple myeloma (MM) cells by inducing cereblon‐mediated degradation of interferon regulatory factor 4, Ikaros (IKZF)1 and IKZF3, transcription factors that are essential for MM cell survival. The mucin 1 (MUC1) C‐terminal transmembrane subunit (MUC1‐C) oncoprotein is aberrantly expressed by MM cells and protects against reactive oxygen species (ROS)‐mediated MM cell death. The present studies demonstrate that targeting MUC1‐C with GO‐203, a cell‐penetrating peptide inhibitor of MUC1‐C homodimerization, is more than additive with LEN in downregulating the WNT/β‐catenin pathway, suppressing MYC, and inducing late apoptosis/necrosis. We show that the GO‐203/LEN combination acts by synergistically increasing ROS and, in turn, suppressing β‐catenin. LEN resistance has been linked to activation of the WNT/β‐catenin→CD44 pathway. In this regard, our results further demonstrate that targeting MUC1‐C is effective against LEN‐resistant MM cells. Moreover, GO‐203 resensitized LEN‐resistant MM cells to LEN treatment in association with suppression of β‐catenin and CD44. Targeting MUC1‐C also resulted in downregulation of CD44 on the surface of primary MM cells. These findings, and the demonstration that expression of MUC1 and CD44 significantly correlate in microarrays from primary MM cells, provide support for combining GO‐203 with LEN in the treatment of MM and in LEN‐resistance.